Villa-Lobos: Collected studies - Peppercorn, L. M. (Cambridge Scolar Press, 1992)
This work brings together in their original format, all of the writings over 51 years of Lisa M. Peppercorn on Villa-Lobos, the leading figure in 20th century Latin American music. They cover his life, family and music and include a selection of his letters.